Aplikasi Satpam Online Dengan Akses Kamera CCTV Untuk Monitoring Keamananan - Sofyan Mufti Presetiyo; Bangun Suprianto; Irfan Alamsah; Jepri Afrizal (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The online security guard application is an application that was first made with imagination and the hope that it is capable and ready to be used to monitor a place using the smart CCTV method, this application has the goal of securing and preventing suspicious movements such as crime or theft that will occurs at a location or residence where this online security application is installed. The method used for making this application is by connecting a smart cctv with a mobile phone which can later monitor anywhere and anytime using the internet network. The result of making and designing this application is that it can be used by anyone on many devices in a practical and effective way to prevent crime.